Comparison of lipid compositions of soft coral Sinularia brassica collected in different coastal regions of Vietnam - Ly, Dang Thi Phuong; Nga, Nguyen Thi; Tuyet, Dang Thi Minh; Quan, Pham Minh; Borisovich, Andrey Imbs (Vietnam Journal of Marine Science and Technology, 2019)
Five soft coral samples belonging to the same specimen Sinularia brassica were collected in the coastal area of Ha Long Quang Ninh, Nhat Le beach, Quang Binh, Hon Vang - Thanh Hoa and Nha Trang areas (2014–2016), these samples were examined and analyzed by total lipid content, content and composition of lipid and fatty acids. Highest total lipid content was found in the sample SHM 09 collected in Nha Trang bay (1.11%), and the lowest total lipid content was in HL-SHM 07 collected in Ha Long, Quang Ninh (0.68%).The lipid composition of samples contained basic classes such as polar lipids, sterols, free fatty acids, triacylglycerols, monoankyldiacylglycerols, hydrocarbons and waxes. In studied soft corals, there are the appearance of all fatty acids from C12 to C24. There are differences in composition and content of lipids and fatty acids in samples collected in different locations: Samples collected at Nha Trang bay contain more polyunsaturated fatty acids than the other samples collected in Ha Long, Thanh Hoa, Quang Binh. Another two samples, collected in Hon Vang (Thanh Hoa) have similar composition and content of lipid classes, the composition and content of fatty acids in total lipids. The obtained results also show the significant impact of habitat and time of acquisition on the studied subject